Development of Visualization System for Agricultural UAV Crop Growth Information Collection. Issue 17 (2018) - Wang, Xu; Sun, Hong; Long, Yaowei; Zheng, Lihua; Liu, Haojie; Li, Minzan
Abstract: It is an important research content to quickly obtain farmland information in precision and intelligent agriculture. Using low-altitude multi-rotor technology, unmanned aerial vehicle (UAV) could help for the rapid collection of real-time farmland information. This paper builds a platform to manage the farmland crop information collected by multi-rotor UAV. Based on the Django framework, designs an information server system for field crop information collection, and collects the positioning data and sensor data from agricultural UAV in real time. Then, the data is analyzed and recorded in the database. The database is used to manage the collected crop data. The data can be downloaded and saved locally from the system. And the crop growth information can be directly reflected in the system to achieve visualization.